How funny is it? Gelotophilia, Katagelasticism and Disparagement Humor - Voutsa, Maria C.; Hatzithomas, Leonidas; Boutsouki, Christina; Zotos, Yorgos (My University, 2016)
The superiority theory supports that the relationship between disparagement humor and perceived humorousness is positive only when identification with the disparaged advertising character is low. The present study elaborates on the superiority theory and tests the interaction effect between disparagement humor, character identification and gelotophilia on attitude toward the ad (Aad) and the brand (Ab). A laboratory experiment indicates that the higher the character identification and the higher (lower) gelotophilia, the more positive (negative) Aad and Ab become, when an advertisement includes disparagement humor compared to non-disparaging appeals. In the case of katagelasticism, a similar interaction effect between disparagement humor and character similarity (an early stage of identification) was found.
Keywords: Superiority theory; Disparagement humor; Gelotophilia